PEMBERANTASAN MAFIA PERADILAN DENGAN PEMBERDAYAAN âGAYA SENTRIFUGALâ DAN âSENTRIPETALâ UKUM DALAM PENEGAKAN SUPREMASI HUKUM (Suatu Kontemplasi Refleksif) - Gunakaya, A. Widiada (Sekolah Tinggi Hukum Bandung, 2010)
Judicial corruption in Indonesia is offenses beyond the reach of the law, Its growth is systemic, not just individual form of corruption, but also shaped, structural, institutional, and political corruption. Such crimes, it can disrupt and inhibit the development of law, hinder the achievement of objectives of the law, threatening the whole system of law, undermine the legal guidance and law enforcement officials, as well as damaging the quality of law enforcement in a fair and dignified. Mitigation efforts should integrate efforts and Penal nonpenal simultaneously. In the law enforcement policy, the instrumental anticorruption law should be empowered to implement the